PEMBENTUKAN KONSEP DIRI REMAJA - Syahraeni, Andi (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2020)
The concept of self for adolescents plays a role so that adolescents can adjust to their environment, so they can be accepted by their environment. Teenagers who have a positive self-concept will have clear goals and ideals for their future. will also have the spirit of life and high morale. The concept of self is an evaluation of a specific domain of self. Teenagers can make a self-evaluation of various domains in their academic life. self-concept is formed based on one's perception of other people's attitudes toward him. In a child, he begins to learn to think and feel himself as determined by others in his environment. the formation of self-concepts between men and women experiences differences. Women in the formation of self-concept comes from the physical state and popularity, while the male self-concept comes from his aggressiveness and strength.